PERAN LAZISNU DALAM MENINGKATKAN SOSIAL EKONOMI MASYARAKAT KECAMATAN KALIBARU KABUPATEN BANYUWANGI - Balya Hidayat; Habibulloh Habibulloh; Samsuri Samsuri; Wisnu Wisnu (Department of Sharia Economics, Faculty of Islamic Economics and Business, Universitas Islam Ibrahimy Banyuwangi, Indonesia, 2021)
One of the worships in Islam is the implementation of zakat, infaq and alms (ZIS). On the other hand, ZIZ is also an effective solution for community economic empowerment. This study aims to elaborate on the socio-economic potential and assistance of the community carried out by LAZISNU in Kalibaru District. The research method uses descriptive qualitative research with NU leaders, LAZISNU managers in Kalibaru District and the beneficiary communities as informants in the study. Data were collected by observation, interviews and documentation. The Miles and Huberman model analysis technique is used as an analytical tool. The results of this study show that the large number of Nahdiyin residents and a solid and competent management/management team have potential in the development of LAZIZNU. There are 3 excellent program models that are continuously being implemented, including: Biasiwa, NUPrenuer, and NUCare as pillars of improving the social economy of the community. In addition, the activation of the NU Deputy Branch Council at the District level, as well as the formation of new branches and UPZIS-UPZIS that can reach muzaqqi and munfiq in remote areas are efforts in institutional optimization.